DETERMINATION OF CONTACT STRESSES IN THE RAILS P50, WHICH ARE OPERATED IN THE METRO - Agarkov, O. V.; Yosyfovych, R. M. (Science and Transport Progress, 2015)
Purpose. In the research one should do: 1) to determine a 3-d stress-strain state of the rail head in contact with the rolling wheels; 2) to analyze different forms of contact interaction; 3) to obtain the data necessary to calculate the durability of railway track rails. Methodology. The basis for calculating the 3-d stress-strain state is the finite element method. The basis for calculating the volume of the stress-strain state is the finite element method. The problem was solved in the elastic 3-D conditions. Real geometrical bodies parameters were used during the solving. Findings. The calculation of the 3-d stress-strain state of the rail head in contact with the rolling wheels for various cases of the contact surfaces geometry is performed. The results of calculation are presented in the graphic and tabular form. The comparison of different options contact conditions is performed. The results are analyzed and conclusions about the optimality conditions of contact interaction are made. Originality. The results of the calculation showed that within the criterion of minimizing the contact stresses in the rails P50 for the conditions specific to the direct contact route section, the use of rolling wheels with a profile according to the drawings of CJSC «MINETEK» is not the most rational decision. The most rational in this case, among the considered is the laying of rails in track with gradient 1:20 and the use of the wheel with the rolling surface profile of 1:10 conicity. The lack of rail gradient eliminates the benefits of the wheel running surface with 1:10 conicity, and a case of contact interaction is the least rational. Practical value. The results of analysis of the contact interaction of the rail head with a rolling stock wheel in a three-dimensional elastic formulation for different conditions of contact interaction were obtained. These data can be used to optimize the conditions of contact interaction and scientific substantiation of the causes of defects of the contact fatigue origin in the railway railhead. The presented models can be upgraded, including the residual stresses in the rails, hardening of the surface layer, and the presence of initial defects as a result of imperfections in the manufacturing process and others in the calculations.